2022
DOI: 10.1186/s12888-022-03896-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of dieting, psychopathological characteristics and maladaptive personality traits in Orthorexia Nervosa

Abstract: Background Pursuing a healthy diet is not a dysfunctional behavior, but dieting could be an important etiological factor for Orthorexia Nervosa (ON). The aim of this study was to investigate the role of diet in groups with high/low orthorexic tendencies. Moreover, some psychopathological characteristics associated with ON and maladaptive personality traits were investigated. Methods The sample consisted of three groups: two were on a diet and had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
0
7
1
Order By: Relevance
“…A study conducted with college students reported that all maladaptive personality traits (negative affectivity, detachment, disinhibition, psychoticism, antagonism) show higher scores in people with higher orthorexic tendencies than those with lower tendencies. 52 Several reasons could explain the differences between our results and previous data. First, our study's mean orthorexia nervosa scores were lower than in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…A study conducted with college students reported that all maladaptive personality traits (negative affectivity, detachment, disinhibition, psychoticism, antagonism) show higher scores in people with higher orthorexic tendencies than those with lower tendencies. 52 Several reasons could explain the differences between our results and previous data. First, our study's mean orthorexia nervosa scores were lower than in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…However, it is not always easy to distinguish healthy eating motivations that may be beneficial for patients from ON. Another important point is that although dieting increases the ON tendency, it alone does not explain ON [ 35 ]. Psychopathological features and maladaptive personality traits should also be considered [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important point is that although dieting increases the ON tendency, it alone does not explain ON [ 35 ]. Psychopathological features and maladaptive personality traits should also be considered [ 35 ]. Alcohol, tobacco, and drug use, social media use, body dissatisfaction, body image, self-esteem, anxiety, depressive symptoms, health literacy are some of these factors [ 15 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the variables most associated with orthorexia nervosa in the literature is perfectionism (Barnes & Caltabiano 2017, Muno 2020, Novara et al 2021, Brytek-Matera et al 2022, Novara et al 2022, Pratt et al 2022.…”
Section: Discussionmentioning
confidence: 99%